The Contribution of Traditional Herbal Medicine Practitioners to Kenyan Health Care Delivery : Results from Community Health-seeking Behavior Vignettes and a Traditional Herbal Medicine Practitioner Survey - Lambert, John; Leonard, Kenneth; Mungai, Geoffrey; Omindi-Ogaja, Elizabeth; Gatheru, Gladys; Mirangi, Mirangi; Owara, Jennifer; Herbst, Christopher H.; Ramana, GNV; Lemiere, Christophe (World Bank, Washington, DC, 2013)
This study examines the role that Traditional Herbal Medicine Practitioners (THMPs) play in Kenya in the context of its human resources for health crisis. Two surveys were carried out to obtain evidence. The first documented the choices and perceptions of households in 36 communities on seeking medical assistance for eight common illnesses. The second survey asked 258 THMPs in five provinces to identify their knowledge sources, training, common illnesses treated, forms of payment, challenges, and concerns. Community-derived data show that households make reasonable decisions when faced with difficult circumstances: they prefer hospitals when these are affordable and seek care at clinics and health centers when hospitals are too far away. There is significant self-care and use of pharmacies, although THMPs are preferred for worms and lower respiratory problems. In general, THMPs provide an important though diminishing role in the provision of health care; they are not sought out in situations when inadequate care is dangerous, specifically infant diarrhoea and potential TB. Whilst Human Resources for Health (HRH) policies are urgently required to strengthen the conventional health workforce and increase their accessibility for the poor, policies should not ignore the findings from this study: many of the rural poor currently receive services from a traditional health workforce not linked to, or regulated by, the national government. This paper argues that formal recognition of their role by the government and by the conventional medical associations, and a targeted strategy to strengthen and build on the positive qualities evident in many traditional medicine practices may be beneficial to safeguarding the well-being of the poor.